2012
DOI: 10.1002/hep.25593
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease is associated with coronary artery calcification

Abstract: Nonalcoholic fatty liver disease (NAFLD) is related to risk factors of coronary artery disease, such as dyslipidemia, diabetes, and metabolic syndrome, which are closely linked with visceral adiposity. The aim of this study was to investigate whether NAFLD was associated with coronary artery calcification (CAC), which is used as a surrogate marker for coronary atherosclerosis independent of computed tomography (CT)-measured visceral adiposity. Out of 5,648 subjects who visited one of health screening centers b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
204
3
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(223 citation statements)
references
References 56 publications
10
204
3
6
Order By: Relevance
“…In addition to an expected risk for disease progression from non-alcoholic steatohepatitis (NASH) to bridging fibrosis, cirrhosis and its complications [1], NAFLD patients are also at higher risk of early asymptomatic cardiovascular alterations and/or frank cardiovascular disease [2]. Specifically, NAFLD, diagnosed either by ultrasonography or by liver biopsy, has been associated with a higher prevalence of low coronary flow reserve [3], coronary calcification [4], and carotid atherosclerosis [5][6][7] well-before the occurrence of cardiovascular events. These alterations have been partly associated with the severity of liver damage, measured by both lobular inflammation and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to an expected risk for disease progression from non-alcoholic steatohepatitis (NASH) to bridging fibrosis, cirrhosis and its complications [1], NAFLD patients are also at higher risk of early asymptomatic cardiovascular alterations and/or frank cardiovascular disease [2]. Specifically, NAFLD, diagnosed either by ultrasonography or by liver biopsy, has been associated with a higher prevalence of low coronary flow reserve [3], coronary calcification [4], and carotid atherosclerosis [5][6][7] well-before the occurrence of cardiovascular events. These alterations have been partly associated with the severity of liver damage, measured by both lobular inflammation and fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast IMT values were found to be significantly higher in diabetic patients regardless of the degree of steatosis by Cakiret al [8] . Similarly other two studies performed in diabetic population reported that hepatic steatosis was not associated with carotid atherosclerosis and suggested that the association of hepatic steatosis and cardiovascular disease might be just an epiphenomenon [9,10] .Targheret al [6] compared carotid IMT in 85 patients with NAFLD and 160 age-, sex-, and BMImatched healthy control subjects and found that the severity Licensed Under Creative Commons Attribution CC BY of liver histopathology in NAFLD patients was strongly associated with early carotid atherosclerosis.. Also Kucukazmanet al [15] in a recent study showed a significant positive correlation between ultrasonographic steatosis grade and mean IMT (r = 0.376, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD, especially in its necroinflammatory form (NASH), may cause atherogenic dyslipidemia [14] . In addition there is an increase of pro-coagulant factors like fibrinogen, plasminogen activator inhibitor-1 and tumor growth factor, which all increase the risk of atherosclerosis [15] . NAFLD is considered to have chronic sub-clinical inflammation and associated with many inflammatory markers.…”
Section: Mechanism (Pathogenesis)mentioning
confidence: 99%
“…In subjects without calcification at baseline, NAFLD significantly affected the development of calcification after adjusting for traditional metabolic risk factors. The severity of NAFLD was dose-dependently associated with the development of CAC Kim et al [15] (2012) Retrospective chart review-4 023 subjects (mean age, 56.9 ± 9.4 yr; 60.7% males) without known liver disease or a history of ischemic heart disease Calcium scoring CT to assess CAC Ultrasound Patients with NAFLD are at increased risk for coronary atherosclerosis independent of classical coronary risk factors, including visceral adiposity.…”
Section: Fatty Liver Indexmentioning
confidence: 99%